Electronically and Orthogonally Tunable SITO Voltage-Mode Multifunction Biquad Filter Using LT1228s - May Phu Pwint Wai; Peerawut Suwanjan; Winai Jaikla; Amornchai Chaichana (My University, 2021)
The commercially available IC LT1228 is an interesting active device due to its advantage features, such as a fast transconductance amplifier, a wide bandwidth over a wide range of voltage gain, low total harmonic distortion (THD), high impedance differential input, etc. The single-input triple-output (SITO) voltage-mode (VM) multifunction biquadratic filters using ICs, LT1228s are introduced in this research. This circuit design provides the three-filtering functions, low-pass (LP), high-pass (HP), and band-pass (BP), without changing the circuit architecture. It comprises three LT1228s, four resistors, and two capacitors connected to the ground. The low impedance voltage output nodes are HP and BP responses. The quality factor (Q) and the pole frequency (ω0) can be electronically and orthogonally tuned by altering the third LT1228’s bias current (IB). The PSPICE simulation and the experiment are verified to describe the circuit operation.
Keywords: Digital biquad filter; Transconductance; High impedance; Analog and Mixed-Signal Circuit Design